2021
DOI: 10.3390/s21010252
|View full text |Cite
|
Sign up to set email alerts
|

Optical Technologies for the Improvement of Skin Cancer Diagnosis: A Review

Abstract: The worldwide incidence of skin cancer has risen rapidly in the last decades, becoming one in three cancers nowadays. Currently, a person has a 4% chance of developing melanoma, the most aggressive form of skin cancer, which causes the greatest number of deaths. In the context of increasing incidence and mortality, skin cancer bears a heavy health and economic burden. Nevertheless, the 5-year survival rate for people with skin cancer significantly improves if the disease is detected and treated early. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 134 publications
0
83
0
Order By: Relevance
“…Melanoma originates from the cells responsible for pigment production (melanocytes) and is the most aggressive of all forms, being likely to grow and spread if left untreated. Therefore, it is vital to diagnose this disease early and start treatment right away [113]. PDT is considered an alternative treatment for melanoma.…”
Section: Malignant Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Melanoma originates from the cells responsible for pigment production (melanocytes) and is the most aggressive of all forms, being likely to grow and spread if left untreated. Therefore, it is vital to diagnose this disease early and start treatment right away [113]. PDT is considered an alternative treatment for melanoma.…”
Section: Malignant Diseasesmentioning
confidence: 99%
“…On the other hand, non-melanoma skin cancers are most commonly found in the areas exposed to the sun [113]. BCC starts from the lower layer of the epidermis (made of basal cells) and tends to grow slowly, with only low metastatic potential [112].…”
Section: Malignant Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluorescent label is the nanoparticles attached to the receptor directed against a biomarker to a specific analyte. [273] Lining et al reported detecting mercury ion (II) using electrospun nanofibers based fluorescent membrane.…”
Section: Fluorescent Sensorsmentioning
confidence: 99%
“…A number of optical methods have been developed for noninvasive in vivo skin diagnostics, including confocal microcopy, fluorescence imaging, and optical coherence tomography. 3 Recently, skin imaging by smartphones under white broadband illumination exploiting the embedded LEDs or ambient light was proposed as a diagnostic modality. 4 8 There are smartphone apps that use the ABCDE criteria, 9 commonly exploited by dermatologists, for analysis of the taken color images of skin neoplasms.…”
Section: Introductionmentioning
confidence: 99%